Clinical and Radiological Outcome of Transforaminal Lumbar Interbody Fusion with Polyether Ether Ketone Cage in Patients with Lumbar Spondylolisthesis - Rishab Chandraprakash; Rajavel Kalirajan; Milap Bhalodiya; Vijayanand Balasubramanian; Gowthaman Nambiraj; Mohan Mahendramani (Journal of Orthopedics and Joint Surgery, 2024)
Aim: Lumbar spondylolisthesis has been a major cause of disability in the general population, mostly in the later part of the productive age-group. Various modes of treatment and surgeries have come up to tackle this morbidity, but with differing results. This study aims to assess clinical and radiological outcomes in patients who underwent transforaminal lumbar interbody fusion (TLIF) with a polyether ether ketone (PEEK) cage for lumbar spondylolisthesis. Materials and methods: A total of 38 patients with varying grades of lumbar spondylolisthesis, among which, 11 males and 27 females were included in this study. All underwent TLIF with PEEK cage surgery. Their preoperative and postoperative pain score, functional scores, and radiological parameters were compared. All patients were followed up to 12 months. Results: The mean preoperative visual analog scale (VAS) started from 8.53 and came to 2.79, postoperatively. Around 68.4% of patients showed minimal disability. Around 60.5% of patients showed excellent outcomes. Around 73.7% of patients showed fusion at 12 months. Near-normal radiological parameters were achieved in all the patients. Five patients showed complications. Conclusion: Overall patient satisfaction was observed in this study, and good radiological outcomes were achieved. The PEEK cage augments the mechanical support provided by TLIF. Clinical significance: The modulus of elasticity of PEEK (3.6 GPa) makes it more closely aligned with cancellous bone (1–20 GPa) compared to traditionally used titanium cages (120 GPa). This alignment contributes to lower rates of bone dehiscence and improved patient outcomes.